Thoracoscopic lung biopsy under regional anesthesia for interstitial lung disease. Issue 4 (16th February 2020) - Kurihara, Chitaru; Tolly, Brian; DeWolf, Andre; Nader, Antoun; Kim, Samuel; Odell, David D; Argento, Angela C; Budinger, G R Scott; Bharat, Ankit
Abstract : Background: Interstitial lung disease (ILD) management guidelines support lung biopsy-guided therapy. However, the high mortality associated with thoracoscopic lung biopsy using general anesthesia (GA) in patients with ILD has deterred physicians from offering this procedure and adopt a diagnostic approach based on high-resolution CT. Here we report that thoracoscopy under regional anesthesia could be a safer alternative for lung biopsy and effectively guide ILD treatment. Methods: This was a single-center retrospective review of prospectively maintained database and consisted of patients who underwent thoracoscopic lung biopsy between March 2016 and March 2018. Patients were divided into two groups: (A) GA, and (B) regional anesthesia using monitored anesthesia care (MAC) and thoracic epidural anesthesia (TEA). Results: During the study period, 44 patients underwent thoracoscopic lung biopsy. Of these, 15 underwent MAC/TEA. There were no significant differences between the two groups with regard to pulmonary function test and clinicodemographic profile. However, operative time and hospital stay were shorter in MAC/TEA group (32.5±18.5 min vs 50.8±18.4; p=0.004, 1.0±1.3 days vs 10.0±34.7 days; p<0.001, respectively). Eight patients in the GA group, but none in the MAC/TEA group, experienced worsening of ILD after lung biopsy (p=0.03). Additionally, one patient in the GA group died due to acute ILD worsening. No cases of MAC/TEA group had to be converted to GA. In all cases a pathological diagnosis could be made. Conclusions: Thoracoscopy using regional anesthesia might be a safer alternative to lung biopsy in patients with ILD.